2016
DOI: 10.1016/j.tranon.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Changes to Blood-Brain Barrier Integrity in Brain Metastasis over Time and after Radiation Treatment

Abstract: INTRODUCTION: The incidence of brain metastasis due to breast cancer is increasing, and prognosis is poor. Treatment is challenging because the blood-brain barrier (BBB) limits efficacy of systemic therapies. In this work, we develop a clinically relevant whole brain radiotherapy (WBRT) plan to investigate the impact of radiation on brain metastasis development and BBB permeability in a murine model. We hypothesize that radiotherapy will decrease tumor burden and increase tumor permeability, which could offer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 34 publications
3
29
1
Order By: Relevance
“…Murrell D.H., et al (2016) did not found changes in BBB permeability at the 1st and 11th days after radiation in mice after WBRT therapeutically relevant doses to human equivalent doses. The results of clinical studies have not revealed an increase in clinical effectiveness in the concurrent use of radiation and chemotherapy [16]. The BBB permeability modification under the influence of radiation on the BM at the moment is controversial and needs further study.…”
Section: Influence Of Radiation Therapy On the Bbb Permeabilitymentioning
confidence: 99%
“…Murrell D.H., et al (2016) did not found changes in BBB permeability at the 1st and 11th days after radiation in mice after WBRT therapeutically relevant doses to human equivalent doses. The results of clinical studies have not revealed an increase in clinical effectiveness in the concurrent use of radiation and chemotherapy [16]. The BBB permeability modification under the influence of radiation on the BM at the moment is controversial and needs further study.…”
Section: Influence Of Radiation Therapy On the Bbb Permeabilitymentioning
confidence: 99%
“…Smith and Lockman used quantitative imaging following injection of dyes and radiolabeled drugs (Lockman et al 2010), the laboratories of Drs. Foster and Chambers used gadolinium CE-MRI and high-resolution anatomic MRI to understand permeability of brain metastases in breast cancer models, and observed it to be heterogeneous (Murrell et al 2016; Murrell et al 2015). The laboratory of Dr. Winkler, confirms such findings of heterogeneity in permeability of brain metastases in a melanoma mouse model.…”
Section: ) Blood-brain Barrier: An Obstacle For Drug Delivery To Bramentioning
confidence: 99%
“…It is critical to realize that the successful treatment of MBM, or any brain metastases, with molecularly-targeted agents will depend on the development of novel therapeutic agents that are not only potent at the target site, but are also capable of penetrating an intact BBB and reaching the protected metastatic tumor cells that are not clinically detectable upon contrast-enhanced MR imaging (Murrell et al 2016). Several critical questions surrounding the clinical diagnoses and treatment of MBM are addressed in this perspective, and adequate drug delivery is a component of each of these critical clinical questions.…”
Section: ) Introductionmentioning
confidence: 99%
“…For example, technological advances in multiphoton laser scanning microscopy have improved our ability to survey single steps of the CNS metastatic cascade via live imaging through a chronic cranial window in vivo [29]. A modified MRI modality has been applied to evaluate the integrity of the blood-brain barrier in mouse model bearing the MDA-MB-213 breast cancer brain metastasis [30]. Intriguingly, the glial cells are activated and have upregulated translocator protein (TSPO) in response to metastasis; thus, agents targeting the upregulated translocator protein (TSPO) on activated glia have been developed for SPECT/PET imaging [31].…”
Section: New Models and Tools To Study Brain Metastasismentioning
confidence: 99%
“…Therefore, there have been extensive efforts recently aiming to understand the biology of tumor-BBB interaction and to find novel ways that facilitate drug delivery through the BBB. To this end, the permeability of blood-brain barrier is highly heterogeneous at sites of metastasis [79,80,30]. Furthermore, pericytes were shown to have significant contribution to the permeability of blood-tumor barrier in multiple experimental breast cancer brain metastasis models [81].…”
Section: New Biological Insights On Brain Metastasismentioning
confidence: 99%